2012
DOI: 10.1021/am201807c
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of S-Nitrosation Processes in Aqueous Polymer Solution for Controlled Nitric Oxide Loading: Toward Tunable Biomaterials

Abstract: An understanding of the nitrosation processes that dictate S-nitrosothiol formation in the presence of a polymer is crucial toward the controlled synthesis of nitric oxide (NO)-releasing materials, an important class of biomaterials that mimic the natural function of cells. Herein, the kinetics of S-nitrosoglutathione (GSNO) formation in the presence of dextran under a variety of nitrosation conditions, including the nitrosating agent and the dextran concentration, are reported. When comparing nitrous acid and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…[46][47][48] We previously demonstrated that because of the lower boiling point and high volatility, t-butyl nitrite ensures complete removal of the nitrosating agent and does not contribute to the overall NO release profile of the resulting materials, and consequently provides an exceptional option for S-nitrosation compared to alkali nitrites. 49,50 The extent of S-nitrosation was monitored by following the UV absorption spectrum of the S-nitrosated dextran derivatives in DI Millipore water. The respective parent dextran thiomer was used for baseline correction.…”
Section: S-nitrosation Of Dextran Thiomersmentioning
confidence: 99%
“…[46][47][48] We previously demonstrated that because of the lower boiling point and high volatility, t-butyl nitrite ensures complete removal of the nitrosating agent and does not contribute to the overall NO release profile of the resulting materials, and consequently provides an exceptional option for S-nitrosation compared to alkali nitrites. 49,50 The extent of S-nitrosation was monitored by following the UV absorption spectrum of the S-nitrosated dextran derivatives in DI Millipore water. The respective parent dextran thiomer was used for baseline correction.…”
Section: S-nitrosation Of Dextran Thiomersmentioning
confidence: 99%
“…The discovery of nitric oxide (NO) as a signaling molecule in many biological functions sparked interest in nitrosation reactions in the 1990s. 1 In recent years, continued interest in nitrosation reactions expanded to development of NO-releasing biomedical materials 2 and regulation of endogenous S-nitroso species 3 as well as to theoretical calculations covering these reactions and subsequent decomposition pathways. 4 Relevant applications of nitrosation reactions extend to azo pigments used in color photography and in cloth dyes 5 and also to chemical gassing of emulsion explosives in mining and construction industries.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nitric oxide is a relatively simple molecule with surprisingly interesting and complex chemistry, eliciting a vast array of studies spanning a range of areas both fundamental and technologically relevant. NO has long been implicated as a pollutant arising from automobile and industrial exhaust, and its atmospheric remediation, generally via the use of a metal or metal oxide catalyst, has become one of the most studied environmental problems. , In addition, NO is an important participant in many biological processes, including blood pressure regulation, vasodilation, and increased biocompatibility for various medical implant devices, , many of which could ideally be monitored via NO-bioimaging . In both atmospheric chemistry and in the context of biological processes, understanding the mechanisms and kinetics of NO reactions with both metal ions and at a range of surfaces is key to improving process performance. Ions, in particular, are critical contributors to the exacerbation of environmentally detrimental NO effects.…”
Section: Introductionmentioning
confidence: 99%